Character Values In The Caci Dance At The Penti Ceremony, Manggarai, NTT - Ni, Laurentius; Wahyu, Yuliana; Edu, Ambros Leonangung (LPPM Universitas PGRI Sumatera Barat, 2024)
This research is motivated by the issue of character among the millennial generation, especially at the local level. The aim of the study is to identify character values in the Caci dance to guide the character formation of the millennial generation. The research method is qualitative. The primary subjects are traditional leaders, community leaders, and male Caci dancers. Field data was obtained through interviews. Data analysis techniques involve grouping, presenting data, analyzing data, and drawing conclusions. The results of the study indicate that the Caci dance reveals theological-ecological values, axiological values, and aesthetic values. The implication of the Caci dance is that Caci players and the young generation of Manggarai are at least holistic humans. They must be clean, pure, and sacred, not involved in moral scandals, such as gambling, conflicts, and free sex, before competing in the Caci arena.